FDG PET/CT Findings in Biliary Papillomatosis. (October 2020) - Tu, Zhuolong; Yang, Yingnan; Ruan, Jing; Tu, Jinfu
Abstract : Abstract: Biliary papillomatosis is a rare disease with high malignant potential. A 64-year-old woman underwent FDG PET/CT, which showed an intense FDG uptake in the location of an aggregated biliary papillomatosis with high-grade intraepithelial neoplasia/carcinoma in situ but did not show FDG uptake in the sporadic, small biliary papilloma. FDG PET/CT may be an effective method to identify the components of the malignant transformation of biliary papillomatosis.